Local Prevalence of Ticks Carrying the Lyme Disease Bacterium - Kruger, Alyssa; Hacker, Madeleine (My University, 2013)
The purpose of this ongoing study has been to survey local deer tick populations in a 50-150 mile radius of Eau Claire for the presence of Borrelia burgdorferi bacteria. This bacterium, which is transmitted by a tick bite, is responsible for Lyme disease in humans and other animals.
Color poster with text, images, graphs, and maps.
Keywords: Ticks as carriers of disease--Testing; Lyme disease--Wisconsin; Borrelia burgdorfei--Testing; Posters